Законодавча регламентація призначення судово-психіатричної експеретизи у кримінальному та цивільному провадженнях - Макарова, О. П.; Makarova, O. P. (Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2023. – № 4. – С. 227-232, 2023)
Здійнено аналіз нормативно-правового регулювання призначення судово-психіатричної експертизи судом або слідчим, зокрема законодавчих та практичних особливостей призначення судово-психіатричних експертиз для з’ясування індивідуально-психологічних особливостей учасників процесу (потерпілих, свідків, підозрюваних). Розглянуто норми Кримінального кодексу України та Цивільного кодексу України, за якими призначається судово-психіатрична експертиза, а також завдання, котрі вона вирішує. Також приділено увагу питанням організації проведення експертизи у спеціалізованих державних установах за наказами та постановами Міністерства охорони здоров’я; окреслено державні установи, на яких покладено функції щодо науково-методичного забезпечення проведення судовопсихіатричних експертиз, а також акцентовано на питаннях підвищення кваліфікації державних судових експертів.

The article analyzes legislative regulations regarding the appointment of a forensic psychiatric examination as ordered by a court or an investigator. A theoretical analysis of the legislative and practical features of the appointment of forensic psychiatric examinations was carried out to clarify the individual psychological characteristics of the participants in the process (victims, witnesses, suspects). The considered articles of the Criminal and Civil Codes of Ukraine, according to which a forensic psychiatric examination is appointed, as well as the considered tasks that it solves. The article also talks about the organization of examination in specialized state institutions according to the Orders and Resolutions of the Ministry of Health; identified state institutions that are entrusted with the functions of scientific and methodological support for the production of forensic psychiatric examinations, as well as the issue of improving the qualifications of state forensic experts. Expertises conducted during criminal or civil proceedings as ordered by the court belong to the categories of judicial. They are appointed by the investigator for the first time in the criminal process at the pre-trial investigation. Forensic examinations are conducted in specialized forensic institutions or in institutions defined by procedural legislation, namely: the Criminal Procedure Code and the Civil Procedure Code of Ukraine. Practically all forensic psychiatric examinations are carried out in specialized forensic departments of state psychiatric institutions according to the rules established by law for the conduct of state forensic institutions. Therefore, the provisions of the Criminal Code and the Criminal Procedural Code of Ukraine, the Civil and Civil Procedural Code of Ukraine enable the legal system to apply special knowledge to participants in criminal and civil proceedings in order to provide the most comprehensive evidence in the case, the purpose of which is to establish the circumstances in criminal or civil proceedings, the protection of persons, state and society from offenses and crimes. Forensic psychiatric examinations are prescribed to find out the individual psychological characteristics of the suspect or accused, witness and victim in the proceedings, and are carried out in institutions designated by the state. They are appointed and conducted when there are grounds for this in the relevant criminal and civil proceedings.

Проанализирована нормативно-правовая база в сфере назначения судебно-психиатрической экспертизы. Определены соответствующие нормы материального и процессуального законодательства – прежде всего уголовного и гражданского. Исследованы подзаконные акты по организации и проведению судебно-психиатрической экспертизы в уголовных производствах.
Legislative support of assignment of forensic psychiatric examination in criminal and civil proceedings
Keywords: законодавча регламентація; судово-психіатрична експертиза; досудове розслідування; кримінальне провадження; цивільне провадження; legislative regulation; forensic psychiatric examination; pre-trial investigation; criminal proceedings; civil proceedings; законодательная регламентация; судебно-психиатрическая экспертиза; досудебное расследование; уголовное производство; гражданское производство